Surfacing Oil: The Oil Industry and Environmental Knowledge in the 20th Century United States - Slane, Cecilia (My University, 2023)
In the 20th century United States, the oil industry expanded internationally, extracting in new environments with new technologies. Throughout this period, contemporary environmental knowledge shaped the oil industry’s perspective on oil extraction and its consequences. In this thesis, I aim to show how the oil industry has used and informed environmental knowledge, such as ecology and marine biology, to argue for certain kinds of production and to defend their practices against critics. This thesis examines three different case studies of the oil industry grappling with the nature of oil: the conservation movement of the early 20th century, Cold War ecological research on the North Slope, and the naturalization of oil via natural oil seep research in California and Rigs-to-Reefs programs in the Gulf of Mexico in the 1960s and 1970s. In these places, the oil industry’s relationship with the environment reaffirmed settler colonial power and questioned the division of nature and technology.
Keywords: Environmental History; History of Science; History, United States